A Challenging Diagnosis: PTEN Hamartoma Tumor Syndrome Presenting as Isolated Soft-tissue Vascular Anomalies. Issue 2 (14th May 2021) - Hill, Lauren R. S.; Duis, Jessica; Kulungowski, Ann M.; Annam, Aparna; Siegele, Bradford; Nakano, Taizo A.
Abstract : Objective: Phosphatase and tensin homolog ( PTEN ) hamartoma tumor syndrome (PHTS) has been known to present with a constellation of congenital anomalies including macrocephaly, vascular malformations, and hamartomas. Identifying a pathogenic germline PTEN mutation early is vital as all patients share a markedly increased risk for malignancy. Diagnosing children, however, is challenging as age-related penetrance makes it difficult to meet established diagnostic criteria. Methods: We present 4 patients with isolated soft-tissue masses of the extremity who lacked the classic constellation of systemic features of PHTS but were found to carry germline PTEN mutations on sequencing performed on involved tissue and subsequently confirmed in peripheral blood specimens. Results: Although none of the patients met published diagnostic criteria to indicate genetic PTEN screening, the growing differential diagnosis of soft-tissue vascular anomalies of the extremity increasingly requires sequencing of involved tissue to accurately characterize a lesion. Diagnosing these patients with a cancer predisposition syndrome radically changed their surveillance regimens which have resulted in the identification of concerning lesions of the thyroid and cervix. Conclusion: PTHS can present as an isolated PTEN hamartomas of soft tissue lesion with minimal systemic findings.